Answer:
<h2>m = 2G² + 5</h2>
Step-by-step explanation:
![G = \sqrt{ \frac{m - 5}{2} }](https://tex.z-dn.net/?f=G%20%3D%20%20%20%5Csqrt%7B%20%5Cfrac%7Bm%20-%205%7D%7B2%7D%20%7D)
To make m the subject square both sides of the equation
That's
![\frac{m - 5}{2} = {G}^{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bm%20-%205%7D%7B2%7D%20%20%3D%20%20%7BG%7D%5E%7B2%7D%20)
Cross multiply
m - 5 = 2G²
Move 5 to the right side of the equation to make m stand alone
We have the final answer as
<h3>m = 2G² + 5</h3>
Hope this helps you
Answer:
(x-3) and (x+3) I think
Step-by-step explanation:
2^3 * 2^-5 = 2^(3 + (-5) = 2^(3 - 5) = 2^-2
For this case we must algebraically rewrite the given expression. So:
x: It is the variable that represents an unknown number
"double a number" is represented as: ![2x](https://tex.z-dn.net/?f=2x)
"6 less than double a number" is represented as: ![2x-6](https://tex.z-dn.net/?f=2x-6)
So, the final expression is: ![2x-6](https://tex.z-dn.net/?f=2x-6)
If we want to rewrite the expression in an equivalent way, we take common factor 2:
![2 (x-3)](https://tex.z-dn.net/?f=2%20%28x-3%29)
Asnwer:
![2x-6](https://tex.z-dn.net/?f=2x-6)
Equivalent expression: ![2 (x-3)](https://tex.z-dn.net/?f=2%20%28x-3%29)
Answer:
p = 2 ; q = 4
Step-by-step explanation:
Given tbe equation :
3p + 2q = 14 - - - (1)
10p + 6q = 44 - - -(2)
What is p and what is q
This is a simultaneous equation ; using elimination method :
Multiply (1) by 6 and (2) by 2
18p + 12q = 84 - - - - (3)
20p + 12q = 88 - - - (4)
Subtract (3) and (4)
-2p = - 4
p = 4/2
p = 2
Put p = 2 in (1)
3p + 2q = 14
3(2) + 2q = 14
6 + 2q = 14
2q = 14 - 6
2q = 8
q = 8/2
q = 4
p = 2 ; q = 4